Survey on CHOKe AQM Family - Vijith, C; Azath, M (International Journal of Computer Sciences and Engineering, 2014)
One of the most important applications in internet is load balancing. For load balancing in IP networks, there are different approaches including Active Queue Management (AQM) which has a proportionate development in research. CHOKe is an AQM method ensures Quality of Service in congested traffic by differentiating responsive flows and unresponsive flows. The survey attempts to study the CHOKe with its descendants and investigates the algorithms based on various congestion metrics and short lived as well as long lived TCP traffic and UDP flows.